The Analysis of Moral Value in Narrative Text of Senior High School English Textbooks - Putri, Anisa Hersa; Maisarah, Ira (Journal of English for Specific Purposes in Indonesia, 2023)
A moral value study is necessary to be taught to students. One way to teach moral values is through literary works such as narrative texts. In this study, the Senior High School English textbooks published by The Ministry of Education and Culture and PT. Grafindo Media Pratama were evaluated on the moral principles provided in their narrative passages. A content analysis design was used in this investigation. The data was derived from seven narrative passages contained in English textbooks. The data were gathered by using a documentation method. The data collection, interpretation, and conclusion were the steps in the data analysis process. This study concentrated on the five moral values criteria listed by Linda and Eyre (2013): kindness, love and affection, honesty, respect, and courage. The study discovered that the virtue of kindness dominated the story texts, while respect was mentioned the least overtly. Furthermore, more study was needed to determine the efficacy of the school's environment in establishing values of morality.